PENGEMBANGAN SISTEM PENGELOLAAN DATA HAK CIPTA PADA SENTRA HKI UNIKAMA MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Saiful Islam; Heri Santoso; Moh. Ahsan (Jurnal Fakultas Teknologi Informasi, 2026)
The management of copyright data at the Intellectual Property Center (HKI) of Universitas PGRI Kanjuruhan Malang (UNIKAMA) is still carried out manually through platforms such as Google Forms and Microsoft Excel, leading to inefficiency, data duplication, and difficulties in monitoring information. This study aims to develop an integrated web-based copyright data management system using the Rapid Application Development (RAD) method. The RAD method was chosen for its ability to accelerate development through fast iterations and active user involvement. The research stages include needs identification through observation and interviews, system design using DFD, ERD, and UML models, and implementation using Laravel, Tailwind CSS, and MySQL. System testing was conducted using the black-box and usability testing method to ensure functionality. The implementation results show that the system successfully integrates submission, validation, and copyright monitoring processes into a single, efficient, real-time platform. The study concludes that applying the RAD method increases development speed and flexibility while improving data management efficiency at the UNIKAMA HKI Center.